Prevalence of chronic kidney disease among the hypertensive patients in Wajir county, Kenya - Ali, Abdirahman M.; Kimani, Harun M.; Ogweno, Gordon O. (International Journal Of Community Medicine And Public Health, 2024)
Background: Chronic kidney disease (CKD) is public health burden and rising rapidly in prevalence in developing countries especially in Sub-Saharan Africa. CKD increases with advancing age and comorbidities like hypertension, diabetes and obesity. However, there is no data on CKD the prevalence and risk factors associated among the hypertensive adult patients in Wajir county. This study aimed at estimating the prevalence and establishing risk factors associated with CKD among hypertensive patients in Wajir county and sought to recommend viable preventive measures. Methods: Analytical cross-sectional study design utilized, non-probability consecutive sampling was adopted to obtain sample size of 293 respondent attending medical outpatient clinic at Wajir county referral hospital between September to December 2023. The study utilised primary data that were collected using structured questionnaires and secondary data from the laboratory result. Results: Key findings revealed majority of hypertensive patients have CKD (45.40%), highlighting a critical health concern in the region. The study found most CKD cases were in early stages (stages 1 and 2), some had progressed to severe stages (stages 4 and 5). Regression analysis identified several demographic and clinical factors associated with CKD development, including age, gender, and education, and employment status, family history of CKD and difficulty in medication compliance. Conclusions: there is high prevalence of chronic kidney disease among hypertensive adults in Wajir county. With nearly half of hypertensive patients also suffering from CKD, there is an undeniable public health crisis at hand in Wajir county. Study recommended initiation of targeted screening programs.